Черные фараоны Египта - Абасов, Н.А. (My University, 2013)
This article is about black pharaohs of Egypt. They ruled country in the 8th century before A.D. Black pharaohs are known as very wise and powerful rulers. The article consist of two parts. The first part is about first Egyptian war against Nubians, the second is about pharaoh Pianxi. Pharaon Pianxi was the greatest ruler of Nubian dynasty. It was 25th Egyptian dynasty. His time is known as golden age of Egyptian history.